In Vivo Confocal Endomicroscopy of Small Intestinal Mucosal Morphology in Dogs. (15th October 2013) - Sharman, M.J.; Bacci, B.; Whittem, T.; Mansfield, C.S.
<x xml:space="preserve">Abstract</x> Background Confocal endomicroscopy (CEM) is an endoscopic technology that permits in vivo cellular and subcellular imaging of the gastrointestinal mucosa. Objective To determine the feasibility of CEM to evaluate small intestinal mucosal topologic morphology in dogs and to characterize the appearance in healthy dogs. Animals Fourteen clinically healthy research colony dogs. Methods Experimental study. Dogs were anesthetized for standard endoscopic evaluation of the small intestine followed by CEM. Two fluorophores were used to provide contrast: fluorescein (10% solution, 15 mg/kg IV) before administration of topical acriflavine (0.05% solution) via an endoscopy spray catheter. A minimum of 5 sites within the small intestine were assessed and at each location, sequential adjustment of imaging depth allowed collection of a three‐dimensional volume equivalent to an 'optical biopsy'. CEM‐guided pinch biopsies were obtained for histologic examination. Results CEM provided high‐quality in vivo cellular and subcellular images. Intravenous administration of fluorescein provided sufficient contrast to allow assessment of the vasculature, cellular cytoplasmic features and goblet cell numbers, and distribution. Topical application of acriflavine preferentially stained cellular nucleic acids, allowing evaluation of nuclear morphology. Quality of captured images was occasionally affected by motion artifact, but improved with operator experience. Conclusion and Clinical Importance CEM provides in vivo images that allow for cellular and subcellular assessment of intestinal mucosal morphology during endoscopy. This has implications for aiding in vivo diagnosis of gastrointestinal disease.